2014
DOI: 10.1002/adsc.201400556
|View full text |Cite
|
Sign up to set email alerts
|

Hydroaminomethylation of Olefins with Aminomethyltrifluoroborate by Photoredox Catalysis

Abstract: A photocatalytic hydroaminomethylation of olefins with N-protected aminomethyltrifluoroborates has been developed. This methodology provides a new strategy for the introduction of a primary aminomethyl group onto electron-deficient C=C bonds. This reaction constitutes a facile entry into synthetically useful g-aminobutyric acid (GABA) derivatives such as baclofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 67 publications
2
56
0
2
Order By: Relevance
“…For example, Koike and Akita 162 along with our laboratory 38 demonstrated that photoredox-catalyzed conjugate additions of α-amino radicals could be applied toward the concise racemic syntheses of baclofen and pregabalin, respectively. In a collaboration with Eli Lilly, Stephenson demonstrated that photoredox-mediated coupling of N -methylmorpholine with pyridazine 92 provides rapid access to an intermediate in the synthesis of JAK2 inhibitor LY2784544 (Scheme 34a).…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…For example, Koike and Akita 162 along with our laboratory 38 demonstrated that photoredox-catalyzed conjugate additions of α-amino radicals could be applied toward the concise racemic syntheses of baclofen and pregabalin, respectively. In a collaboration with Eli Lilly, Stephenson demonstrated that photoredox-mediated coupling of N -methylmorpholine with pyridazine 92 provides rapid access to an intermediate in the synthesis of JAK2 inhibitor LY2784544 (Scheme 34a).…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…[1][2][3] The most studied methods for the generation of a-aminoalkyl radicals include photoredox catalyzed abstraction of the hydrogen at a-carbon of the nitrogen atom of alkyl amines 1 and the desilylation of a-silylamines. In this context, various protocols have been developed, particularly for the formation and addition of a-aminoalkyl radicals pecies.…”
mentioning
confidence: 99%
“…In this context, various protocols have been developed, particularly for the formation and addition of a-aminoalkyl radicals pecies. [3] On the other hand, the silver-catalyzed decarboxylative generation of alkyl radicals from aliphatic carboxylic acids has been extensively reported as ag eneral method for the synthesis of alkyl compounds. [2] Several examples using the deborylation of a-borylamines have also been reported.…”
mentioning
confidence: 99%
“…The intermediacy of α-amino radicals to elaborate aryl- and heteroaryl substructures has recently been demonstrated in photoredox catalysis [6,25,28,36] from both unfunctionalized amines (toward the preparation of JAK2 inhibitor LY2784544), [6] and those with the TMS [35,37,38] and CO 2 H [2,39] activating groups (Scheme 1). …”
mentioning
confidence: 99%